THE MIOCENE BESCHCHEUL HORIZON OF WEST SIBERIA: STRATIGRAPHY, PALEOBOTANY, AND PALEOMAGNETISM - Martynov V.A.; Nikitin V.P.; Gnibidenko Z.N. (My University, 2000)
The mid-Miocene in West Siberia was marked by significant environmental changes related to development of the river system in response to the uplift of the mountainous framing structures. This resulted in formation of the lateral succession of several alluvial formations and in the landscape reorganization that affected, in particular, vegetation (the gradual replacement of the mesophilic Turgai flora by the post-Turgai forest-steppe formations). These changes are recorded in the Beshcheul Horizon representing the boundary stratigraphic unit of the region, above which the Oligocene to lower-middle Miocene succession of humid gray-colored deposits of the West Siberian platform cover is replaced by a new semiarid sedimentary sequence accumulated in the second half of the Miocene-Pliocene time. In this work, we consider reference sections of the horizon (Irtysh and Ob' river basins) and their biostratigraphic and paleomagnetic characteristics. On the basis of summarizes paleobotanical data collected over many years, the evolution of the post-Turgai flora and its most important stages are outlined. The composite magnetostratigraphic section of the horizon, with five major zones of normal and reversed polarities, is also compiled. Based on the available data, the stratigraphic range of the horizon is assumed to be corresponding to the Burdigalian-Serravalian.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен